2016
DOI: 10.4103/2249-4863.192365
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome in patients admitted with acute exacerbation of chronic obstructive pulmonary disease in a rural Tertiary Care Center

Abstract: Background:Chronic obstructive pulmonary disease (COPD) is associated with a high degree of mortality and morbidity around the world with the burden of the disease being more in the developing countries. In the Indian context data is limited. This study was carried out to determine the predictors of outcome in patients admitted with acute exacerbation of COPD in a rural Tertiary Care Center in the state of Kerala.Materials and Methods:This was a prospective cohort study. Patients admitted with acute exacerbati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…21 Although the final multivariable analysis did not fulfil other prior hypotheses of those laboratory parameters, some of our observations were supported by past studies such as hypoalbuminemia, 16 39 hyponatremia, 39 hypochloremia, 40 eosinopenia 16 and anaemia. 41 Hyponatremia is a common predictive marker of mortality and morbidity of AECOPD patients, although the effect found in our study was modest and non-significant. 40 Generally, all admitted AECOPD patients are administered with systemic corticosteroids during their admission in our setting, both intravenous and oral route.…”
Section: Open Accesscontrasting
confidence: 70%
“…21 Although the final multivariable analysis did not fulfil other prior hypotheses of those laboratory parameters, some of our observations were supported by past studies such as hypoalbuminemia, 16 39 hyponatremia, 39 hypochloremia, 40 eosinopenia 16 and anaemia. 41 Hyponatremia is a common predictive marker of mortality and morbidity of AECOPD patients, although the effect found in our study was modest and non-significant. 40 Generally, all admitted AECOPD patients are administered with systemic corticosteroids during their admission in our setting, both intravenous and oral route.…”
Section: Open Accesscontrasting
confidence: 70%
“…In contrast to our study, several other studies showed that AECOPD were more commonly seen in males. 1,2,[11][12][13][14] The gender difference was not significant in our study.…”
Section: Discussionmentioning
confidence: 66%
“…Studies have shown the coexisting illness like diabetes and hypertension in COPD as well as AECOPD patients. 1,11,13,14 Diabetes among COPD was seen in 3.1% patients in a study done by Jain et al 11 Ittyachen et al 14 also showed diabetes in 27.1% and hypertension in 28.6% of COPD patients. Koo et al 1 showed coexisting diabetes in 18.0% and hypertension in 52.6% of COPD cases.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation